An atom-economical addition of methyl azaarenes with aromatic aldehydes via benzylic C(sp3)–H bond functionalization under solvent- and catalyst-free conditions - Yennamaneni, Divya Rohini; Amrutham, Vasu; Gajula, Krishna Sai; Banothu, Rammurthy; Boosa, Murali; Nama, Narender (Beilstein Journal of Organic Chemistry, 2020)
A convenient practical approach for the synthesis of 2-(pyridin-2-yl)ethanols by direct benzylic addition of azaarenes and aldehydes under catalyst- and solvent-free conditions is reported. This reaction is metal-free, green, and was carried out in a facile operative environment without using any hazardous transition metal catalysts or any other coupling reagents. Different aromatic aldehydes and azaarenes were monitored, and the yields of the resulting products were moderate to excellent. We accomplished several azaarene derivatives under neat conditions through a highly atom-economical pathway. To evaluate the preparative potential of this process, gram-scale reactions were performed up to a 10 g scale.
Keywords: aldehydes; azaarenes; benzylic addition; green chemistry; solvent-free conditions